Standard specification for Naval Brass Rod, Bar, and Shapes (American Society of Testing Materials, 2006)
This specification establishes the requirements for naval brass rod, bar, and shapes produced from Copper Alloy UNS Nos. C46200, C46400, C47940, C48200, or C48500.